2010
DOI: 10.1007/s11708-010-0134-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wind energy potential in Gaza Strip

Abstract: The analysis of collected wind data at two sites in the Gaza Strip, namely, Gaza City and Gaza International Airport in Rafah city, is presented. The two sites are candidates for remote area wind energy applications. The purpose of this paper is to present the results of the assessment of wind energy potential in the Gaza Strip in order to evaluate the wind regimes for installing wind energy conversion systems for power generation. The data on wind speed, direction and frequency distribution are used to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…However, Elnaggar confirmed, depending on the data for a typical meteorological year from 1991 to 2010, that the average monthly speed in Gaza at 10 m high, mostly exceeds 4 m/s, except for October and November [29]. This result is very close to Badawi's result [39]. The expected annual energy output in Gaza from a small wind turbine of 5 kW at a height of 10 m amounts to 2695 kWh.…”
Section: Monthssupporting
confidence: 53%
See 1 more Smart Citation
“…However, Elnaggar confirmed, depending on the data for a typical meteorological year from 1991 to 2010, that the average monthly speed in Gaza at 10 m high, mostly exceeds 4 m/s, except for October and November [29]. This result is very close to Badawi's result [39]. The expected annual energy output in Gaza from a small wind turbine of 5 kW at a height of 10 m amounts to 2695 kWh.…”
Section: Monthssupporting
confidence: 53%
“…This result corresponds to the results Elnaggar was found. Alaydi concluded that the annual highest attainable wind power potential per unit area of the wind stream is about 0.5 MWhr/m 2 /year [27,28,39]. [29].…”
Section: Monthsmentioning
confidence: 99%
“…To accentuate the importance of evaluation of wind energy potential across the scales, a few selected studies have been briefly reviewed here. Alaydi (2011) analysed the collected wind data at two sites in the Gaza strip, namely, Gaza city and Gaza international airport in Rafah city and these cities were recommended for wind energy exploitation in the Gaza strip. Ajayi et al (2011) assessed the potential viability of wind resource potential in Jos, Plateau State, Nigeria for power generation based on the monthly mean wing speeds of 1987-2007 and it was concluded that Jos was a suitable site for wind farm projects of varying sizes and that MW-h to GW-h of electricity was likely to be produced per period of months, seasons and years.…”
Section: Introductionmentioning
confidence: 99%
“…To accentuate the importance of evaluation of wind energy potential across the scales, a few selected studies have been briefly reviewed here. Alaydi (2011) analysed the collected wind data at two sites in the Gaza strip, namely, Gaza city and Gaza international airport in Rafah city and these cities were recommended for wind energy exploitation in the Gaza strip. Ajayi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Alaydi 154 also applied the Power Law Profile equation to estimate the wind power density extrapolated to a height of 50 m from measurements made at a height 10 m and used a two-parameter Weibull distribution model at two sites of Palestine. In the Gaza Strip, reporting an average wind speed of 4.2 m/s and maximum wind speed of 5 m/s for 60% of the time with a power density of 186.5 W/m 2 , (Form factor λ = 3.52, scale factor κ = 1.9).…”
Section: Exploration Of Wind Resources Using Traditional and Modern Mmentioning
confidence: 99%